(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article focuses on the linguistic concepts of terminology and a term system, provides the views of linguists on the definition and differentiation of these terms, explains the semantics of the word and the term, as well as the role of the cognitive approach in modern terminology. The scientific work defines a concept and a category, and describes the role of the processes of conceptualization and categorization in English terminology. As more than 90 % of new words appearing in modern languages are vocabulary for special purposes, it is increasingly important to study the ways of their formation. The research is relevant since it provides a deeper understanding of the structure and content of concepts that underlie the formation of language categories, the mechanisms of interaction between cognitive and language structures in the process of forming the terminological meaning.